Barriers and facilitators to nursing delirium screening in older emergency patients: a qualitative study using the theoretical domains framework. (17th January 2022) - Eagles, Debra; Cheung, Warren J; Avlijas, Tanja; Yadav, Krishan; Ohle, Robert; Taljaard, Monica; Molnar, Frank; Stiell, Ian G
Abstract: Background: delirium is common in older emergency department (ED) patients, but vastly under-recognised, in part due to lack of standardised screening processes. Understanding local context and barriers to delirium screening are integral for successful implementation of a delirium screening protocol. Objectives: we sought to identify barriers and facilitators to delirium screening by nurses in older ED patients. Methods: we conducted 15 semi-structured, face-to-face interviews based on the Theoretical Domains Framework with bedside nurses, nurse educators and managers at two academic EDs in 2017. Two research assistants independently coded transcripts. Relevant domains and themes were identified. Results: a total of 717 utterances were coded into 14 domains. Three dominant themes emerged: (i) lack of clinical prioritisation because of competing demands, lack of time and heavy workload; (ii) discordance between perceived capabilities and knowledge and (iii) hospital culture. Conclusion: this qualitative study explored nursing barriers and facilitators to delirium screening in older ED patients. We found that delirium was recognised as an important clinical problem; however, it was not clinically prioritised; there was a false self-perception of knowledge and ability to recognise delirium and hospital culture was a strong influencer of behaviour. Successful adoption of a delirium screening protocol will only be realised if these issues are addressed.